2021
DOI: 10.1080/22221751.2021.1925594
|View full text |Cite
|
Sign up to set email alerts
|

Germline IGHV3-53-encoded RBD-targeting neutralizing antibodies are commonly present in the antibody repertoires of COVID-19 patients

Abstract: Monoclonal antibodies (mAbs) encoded by targeting the spike receptor-binding domain (RBD) have been isolated from different COVID-19 patients. However, the existence and prevalence of shared VH3-53-encoded antibodies in the antibody repertoires is not clear. Using antibody repertoire sequencing, we found that the usage of VH3-53 increased after SARS-CoV-2 infection. A highly shared VH3-53-J6 clonotype was identified in 9 out of 13 COVID-19 patients. This clonotype was derived from convergent gene rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 67 publications
4
46
0
Order By: Relevance
“…We also observed a variable IgG PB response against the RBD early during infection, likely influenced by the heterogeneity in presymptomatic incubation period that led to the detection of RBD-reactive IgG PB at earlier sampling visits. Alternatively, it has been shown that human populations are poised to response to RBD based on multiple studies describing the public IGHV3-53 gene segment being overrepresented in convalescent individuals with the remarkable feature of requiring minimal mutation to achieve high affinity binding [39][40][41][42][43]. Our observation on the SARS-CoV-2-reactive MBCs also showed early formation of the RBD-reactive IgG MBCs, consistent with the notion that RBD-reactive B cells can emerge rapidly following exposure.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed a variable IgG PB response against the RBD early during infection, likely influenced by the heterogeneity in presymptomatic incubation period that led to the detection of RBD-reactive IgG PB at earlier sampling visits. Alternatively, it has been shown that human populations are poised to response to RBD based on multiple studies describing the public IGHV3-53 gene segment being overrepresented in convalescent individuals with the remarkable feature of requiring minimal mutation to achieve high affinity binding [39][40][41][42][43]. Our observation on the SARS-CoV-2-reactive MBCs also showed early formation of the RBD-reactive IgG MBCs, consistent with the notion that RBD-reactive B cells can emerge rapidly following exposure.…”
Section: Discussionsupporting
confidence: 88%
“…For OD values greater than 4, a value of 4 is assigned. Furthermore, we have compared the binding of WT, N501Y and N501Y-E484K RBD with a SARS-CoV-2 human antibody which was produced as previously described with modifications [26] . Briefly, SARS-CoV-2 RBD-specific memory B cells were sorted by multi-laser AriaII sorter (BD Biosciences, New Jersey, USA) from SARS-CoV-2 infected individuals.…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic of antibody responses induced by SARS-CoV-2 infection requires more systematic and in-depth research on a larger cohort over a longer period. Antibodies identified from these shared spike-specific clusters possess binding and neutralizing activities, as demonstrated in our recent report that synthesized a repertoire-deduced IGHV3-53-encoded heavy chain paired with a common IGKV1-9 light chain were successfully expressed in transfected HEK293 cells and showed RBD binding and virus-neutralizing activities ( 82 ).…”
Section: Discussionmentioning
confidence: 82%
“…This study identified 13 shared clusters that were highly relevant with known neutralizing antibodies isolated from COVID-19 patients. Recent reports showed that IGHV3-53 and IGHV3-30 encode convergent antibodies targeting the RBD of spike protein ( 5 , 72 , 80 82 ). These results supported that SARS-CoV-2 induced convergent antibody response across different patients, which can be identified by querying antibody sequencing repertoires.…”
Section: Discussionmentioning
confidence: 99%